Evaluation of acetylcholinesterase source from fish, Tor tambroides for detection of carbamate - Ahmad S.A.; Sabullah M.K.; Shamaan N.A.; Shukor M.Y.A.; Jirangon H.; Khalid A.; Syed M.A. (Triveni Enterprises, 2024)
Indexed by Scopus